Oogenesis in Phragmatopoma (Polychaeta: Sabellariidae): Evidence for morphological distinction among geographically remote populations - Faroni-Perez, Larisse [UNESP]; Zara, Fernando José [UNESP] (My University, 2014)
The Southwest Atlantic Ocean sand-reef building polychaete, Phragmatopoma lapidosa, was recently synonymised with Phragmatopoma caudata based on morphological characters. This study uses histochemical and ultrastructural procedures to describe oogenesis in Phragmatopoma caudata from the Southwest (SW) Atlantic and make a comparison with previously published data for the Northwest Atlantic (NW) forms. In the South American worms, the exposed ovary consists of simple groups of oogonia attached to blood vessels, unlike the NW Atlantic worms in which only the proliferative and previtellogenesis phases of the oocytes are associated with blood vessels. In SW Atlantic worms, the oocytes float in the coelom during the vitellogenic phase. We discovered several heterogeneous features (e.g., cell extensions, amoeboid cells, ovary capsule, active uptake of material from blood vessels and egg envelope) that can be used to distinguish between North and South Hemisphere populations of P. caudata. In light of the observed divergence between worms from these separated populations, our findings support reproductive plasticity. The present study reveals biodiversity within sand-reef making sandcastle worms.
Keywords: Benthic invertebrates; Geographic plasticity; Histochemistry; Histology; Ovary; Reproductive biology; Ultrastructure; Worm reefs